Conflict Resolution and Crisis Communication. Transforming Conflicts and Building Peace (2nd edition) - HERȚA, Laura-Maria; POP-FLANJA, Delia (2023)
This volume aims to bring together articles which present, explore, analyse andinterpret salient events from the international arena. The focus falls on those phenomena andevents which have a global outreach and which impact entire communities, as well asindividuals and domestic/sub‐state groups. Traditionally, the analysis of international politicsused to evoke a Realist view and mind‐set and, starting with the 1970s, a Neorealist outlook,according to which phenomena occurring in world politics generated reactions from stateactors and, hence, state interaction and state behaviour were observed and commented on.